2018
DOI: 10.1007/s00415-018-8959-8
|View full text |Cite
|
Sign up to set email alerts
|

Low specificity of voltage-gated calcium channel antibodies in Lambert–Eaton myasthenic syndrome: a call for caution

Abstract: As testing for neuronal antibodies become more readily available, the spectrum of conditions potentially associated with these autoantibodies has been widening. Voltage-gated calcium channel antibodies (VGCC-Ab) are no exception to this trend. The significance of an elevated VGCC-Ab titer beyond its original clinicopathological correlate, Lambert-Eaton myasthenic syndrome (LEMS) remains undetermined. We sought to determine the diagnostic significance of an elevated serum VGCC-Ab titer in a large single-center … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…P/Q type VGCC antibodies have been reported to be very sensitive and specific for the diagnosis of LEMS [16,17], although low titers could be found also in controls, in patients with various types of cancers as well as in patients with amyotrophic lateral sclerosis [16,57]. However, a recent study observed the presence of these antibodies in a high proportion of patients without a neurological autoimmune or inflammatory etiology, with no difference in antibody titers between the autoimmune and the not-autoimmune groups [58], confirming that the P/Q type VGCC antibodies are not diagnostic in the absence of clinical and electrophysiologic features of LEMS. No correlation has been found between antibody titers and clinical features or outcome, although antibody levels might decrease after immunosuppressive treatment [59,60].…”
Section: Clinical Features and Diagnosismentioning
confidence: 99%
“…P/Q type VGCC antibodies have been reported to be very sensitive and specific for the diagnosis of LEMS [16,17], although low titers could be found also in controls, in patients with various types of cancers as well as in patients with amyotrophic lateral sclerosis [16,57]. However, a recent study observed the presence of these antibodies in a high proportion of patients without a neurological autoimmune or inflammatory etiology, with no difference in antibody titers between the autoimmune and the not-autoimmune groups [58], confirming that the P/Q type VGCC antibodies are not diagnostic in the absence of clinical and electrophysiologic features of LEMS. No correlation has been found between antibody titers and clinical features or outcome, although antibody levels might decrease after immunosuppressive treatment [59,60].…”
Section: Clinical Features and Diagnosismentioning
confidence: 99%
“…13 Elevated voltage-gated calcium channel antibodies have frequently been found in both healthy controls and non-autoimmune conditions, including neurodegenerative conditions, and the voltage-gated calcium channel antibody positivity has been hypothesized to be a downstream effect due to neuronal injury following a non-specific immune activation due to a primary underlying disease process. 14,15 The co-existence of MOG antibodies and voltage-gated calcium channel antibodies is not well-documented; however because MOG antibodies have been shown to cause similar presentations in adults without the co-existence of voltage-gated calcium channel antibodies, the N-type calcium channel and GAD65 antibodies likely do not represent significant findings in our patient.…”
Section: Discussion/conclusionmentioning
confidence: 74%
“…Interestingly, recent researches reported that antibodies against VGCC were detected not only in other autoimmune diseases, such as MG, but also in healthy people, which questioned the specificity of antibodies against VGCC for LEMS diagnosis. Di Lorenzo found that antibodies against P/Q-type VGCC had a diagnostic sensitivity of 88.89% and specificity of 36.17% (58). Zalewski also reported that antibodies against P/Q-type VGCC have a compromised specificity on LEMS diagnosis (59).…”
Section: Lemsmentioning
confidence: 99%